The Effects of Fear of Missing Out (FOMO) and Hedonistic Lifestyle on the Financial Behavior of Generation Z Women in Makassar - Asniwati Asniwati; Andi Dewi Angreyani; Nurhaeda Nurhaeda; Charisma Ekawaty (Entrepreneurship, Management, and Business Research Journal, 2026)
The rapid development of digital technology and social media has significantly influenced the financial behavior of Generation Z, particularly among women who demonstrate a high level of engagement with social media platforms. The phenomena of Fear of Missing Out (FoMO) and a hedonistic lifestyle are considered factors that may affect how individuals manage their finances. This study aims to examine the influence of FoMO and hedonistic lifestyle on the financial behavior of Generation Z women. This research employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to Generation Z women and analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. The results indicate that FoMO has a positive and significant effect on financial behavior, with a path coefficient of 0.457, a t-statistic value of 11.050, and a p-value of 0.000. Similarly, a hedonistic lifestyle has a positive and significant effect on financial behavior, with a path coefficient of 0.503, a t-statistic value of 12.370, and a p-value of 0.000. Furthermore, the coefficient of determination (R²) of 0.613 indicates that FoMO and hedonistic lifestyle simultaneously explain 61.3% of the variance in the financial behavior of Generation Z women, while the remaining 38.7% is influenced by other factors outside the research model. These findings suggest that higher levels of FoMO and stronger hedonistic lifestyle tendencies among Generation Z women are associated with a greater influence on their financial behavior. This study contributes to the development of the financial behavior literature and provides valuable insights for various stakeholders in enhancing financial awareness and financial management capabilities among Generation Z women.